A Single Bout of High-Intensity Interval Training Improves Motor Skill Retention in Individuals With Stroke. (August 2017) - Nepveu, Jean-Francois; Thiel, Alexander; Tang, Ada; Fung, Joyce; Lundbye-Jensen, Jesper; Boyd, Lara A.; Roig, Marc
Background . One bout of high-intensity cardiovascular exercise performed immediately after practicing a motor skill promotes changes in the neuroplasticity of the motor cortex and facilitates motor learning in nondisabled individuals. Objective . To determine if a bout of exercise performed at high intensity is sufficient to induce neuroplastic changes and improve motor skill retention in patients with chronic stroke. Methods . Twenty-two patients with different levels of motor impairment were recruited. On the first session, the effects of a maximal graded exercise test on corticospinal and intracortical excitability were assessed from the affected and unaffected primary motor cortex representational area of a hand muscle with transcranial magnetic stimulation. On the second session, participants were randomly assigned to an exercise or a nonexercise control group. Immediately after practicing a motor task, the exercise group performed 15 minutes of high-intensity interval training while the control group rested. Twenty-four hours after motor practice all participants completed a test of the motor task to assess skill retention. Results . The graded exercise test reduced interhemispheric imbalances in GABAA -mediated short-interval intracortical inhibition but changes in other markers of excitability were not statistically significant. The group that performed high-intensity interval training showed a better retention of the motor skill. Conclusions . The performance of a maximal graded exercise test triggers only modest neuroplastic changes in patients with chronic stroke. However, a single bout of high-intensity interval training performed immediately after motor practice improves skill retention, which could potentially accelerate motor recovery in these individuals.